2021
DOI: 10.3393/ac.2020.09.14.1
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation in the Use of Diverting Loop Ileostomy in Australia and New Zealand Colorectal Surgeons

Abstract: What does this paper add to the literature? This survey of Australian and New Zealand surgeons examines the use of diverting ileostomies in two common scenarios along with the use of both transanal tubes and pelvic drains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…They found no difference in mortality or AL rate 18 . For surgeons who selectively employ pelvic drains, the ability of measure DFA is another factor to consider 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no difference in mortality or AL rate 18 . For surgeons who selectively employ pelvic drains, the ability of measure DFA is another factor to consider 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 For surgeons who selectively employ pelvic drains, the ability of measure DFA is another factor to consider. 19 Pelvic operations with a low anastomosis were chosen for study as the drain will sit in a confined space adjacent to the anastomosis and in a dependent position where fluid would be predicted to accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic drains remain controversial [44][45][46], but a survey of Australian and New Zealand surgeons found that most respondent surgeons still use peritoneal drainage for extra-peritoneal anastomoses. Overall, 46% of surgeons use a pelvic drain for all cases and the remaining 54% report using pelvic drains selectively [47].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is geographical variation in the strategy regarding TDI usage in Australia and New Zealand, with a statistically significant difference in the use of mandatory TDIs in ileal pouch surgery (P = 0.029). 4 Australasian surgeons employ a TDI in 89% of rectal cancer resections, whilst reporting an AL rate of 5.2%. 5 AL is an uncommon event, so how do we reconcile the morbidity and inconvenience that patients with a TDI, and who do not leak, are subjected to?…”
Section: Does An Ileostomy Cover the Surgeon Or The Anastomosis?mentioning
confidence: 99%
“…16 When surgeons were asked at what rate do they consider a TDI is in their patients' best interest, the mean response was 15% for low colorectal anastomoses and 10% for ileal pouches. 4 If a surgeon believes that their overall AL rate is below that threshold figure, then it would be in their patients' interest to omit the TDI.…”
Section: Does An Ileostomy Cover the Surgeon Or The Anastomosis?mentioning
confidence: 99%